KUALITAS KEBERSIHAN LINGKUNGAN SEBAGAI PENUNJANG DAYA TARIK WISATA PANTAI SANUR KAJA - Sara Violina; Ida Bagus Suryawan (JURNAL DESTINASI PARIWISATA, 2016)
ABSTRACT Northern Sanur Beach (Sanur Kaja Beach) consisting of Matahari Terbit Beach and the main Sanur Beach is a polular tourist destination on the island of Bali. Its strategic location, famous history, public and additional facilities, makes Sanur a demanding location for tourists. But one important role for such tourist destination is the cleanliness of the beach itself, providing comfort to travellers. A direct observational study and a descriptive cross-sectional study with randomized survey of 100 travellers (50 domestic and 50 international) regarding the cleanliness of Northern Sanur beach. Through the survey we gathered traveller’s evaluation on current sanitation of public facility (toilet, parking, and resting), additional facilities (restaurant, gift shop, and street vendors), and sanitary facility (rubbish bins) condition in Northern Sanur beach giving a score of very clean, moderate, or poor. Through direct observational we looked at physical objects around the environement such as its geography and facilities available in Northern Sanur beach collected through interviews from local informans. Respondents showed an overall positive response of “moderate” 25 of respondents or (50%) of domestics, and 32 respondents or (64% ) foreigners regarding sanitation quality of Northern Sanur beach. Public facilities as well as additional facilities are generally considered to be moderately clean by the total respondents. But traveller’s opinion suggested the “poor” availability of rubbish bins 25 of respondent or (50%) domestics and 23of respondents or  (46%) foreigners. Public facilities of four public toilets, two parking area, rubbish bins, are available for travellers and taken care by local employees assigned by the head of village. As travellers states Northern Sanur to be moderately clean, other results that are considered poor or below expectation regarding specific public facilities should be taken care of to provide a better tourist attraction. Cleanliness is a tourist attraction itself, therefore keeping clean it is important for the sustainability of tourism.